Peran Lembaga Swara Parangpuan Sulawesi Utara dalam Meminimalisir Kekerasan dalam Rumah Tangga Perspektif Gender dan Hukum Islam - Al Ahyar Mokodompit; Ahmad Rajafi; Frangky Suleman (SPECTRUM: Journal of Gender and Children Studies, 2021)
This study aims to determine the role of the North Sulawesi Swara Parangpuan Institution in minimizing domestic violence (KDRT) by using a gender perspective on the causes of KRDT, because Swara Parangpuan is an institution that focuses its activities on issues of violence against women. Moreover, the role of the institution is observed from the perspective of Islamic law. The research method used is a qualitative with a starting point on a descriptive analytical approach to obtain data related to the role of the Swara Parangpuan Institution with observations and interviews. In addition, a literature study was also conducted in order to find theories relevant to the research. This study found that the number of domestic violence both nationally and locally (North Sulawesi) showed a massive number. The available data also finds that women are the most vulnerable to become victims of domestic violence, therefore the gender perspective is very relevant in this study. Based on this, the role of the North Sulawesi Swara Parangpuan Institution is very important in minimizing domestic violence, especially in digging up victim information related to field facts through communicative and persuasive approaches. This role is manifested in its activities, as well as its advocacy agenda: individual counselling, consultation, and collecting relevant information. The perspective of Islamic law in this role is in accordance with the benefit values ​​contained in the Qur'an. Abstrak Penelitian ini bertujuan untuk mengetahui peran Lembaga Swara Parangpuan Sulawesi Utara dalam meminimalisir kekerasan dalam rumah tangga (KDRT) dengan menggunakan perspektif gender pada sebab-sebab terjadinya KRDT, sebab Swara Parangpuan adalah lembaga yang memfokuskan kegiatan-kegiatannya pada isu-isu kekerasan terhadap perempuan. Sementara peran dari Lembaga tersebut ditinjau dari perspektif hukum Islam. Metode penelitian yang digunakan adalah penelitian kualitatif dengan bertitik tolak pada pendekatan analitis deskriptif untuk mendapatkan data terkait dengan peran Lembaga Swara Parangpuan dengan pengamatan dan wawancara. Selain itu, studi literatur juga dilakukan guna menemukan teori-teori yang relevan dengan penelitian. Penelitian ini menemukan bahwa angka KDRT secara nasional, maupun lokal (Sulawesi Utara) menunjukan angka yang masif. Data yang ada juga menemukan bahwa yang rentan menjadi korban KDRT adalah perempuan, oleh karena itu perspektif gender sangat relevan dalam penelitian ini. Berdasarkan hal tersebut peran Lembaga Swara Parangpuan Sulawesi Utara sangat penting peranannya dalam meminimalisir KDRT, terutama dalam menggali informasi korban terkait dengan fakta-fakta lapangan melalui penekatan komunikatif dan persuasif. Peranan tersebut terejawantahkan dalam kegiatan-kegiatannya, serta agenda advokasinya: konseling individu, konsultasi, serta informasi-informasi yang relevan. Perspektif hukum Islam dalam peranan ini sesuai dengan nilai kemaslahatan yang tertuang dalam Al-Qur’an.